Evaluating the Impact of Uncertainties in Groundwater Modelling A case study of a glaciofluvial deposit investigating the effects of different boundary conditions using multiple numerical models - DJERF, KLARA; HASSELBERG, JOSEFIN (My University, 2023)
Abstract The demand for drinking water is constantly increasing around the world, which partly entails an increased demand for groundwater of decent quality and quantity. Since ground water is hidden beneath the ground, it is difficult to obtain a detailed comprehension of the hydrogeological conditions of an aquifer system. Groundwater modelling is a useful tool to increase the understanding of a current groundwater system and can be used to simulate future scenarios and events. The aim of this thesis is to set up several groundwater models and evaluate the impact of uncertainties regarding the conceptual understanding of boundary conditions. The models are based on an aquifer system located in a glaciofluvial deposit outside of Umeå Municipality (Sweden), where several geological and hydrogeological investigations have been conducted. Based on a conceptual model of the study area, a numerical model is set up with MODFLOW2005, to analyse how different boundary conditions affect the model results. Manual calibration is performed on parameter values and sensitivity analysis of different boundary conditions. The findings indicate that all the examined boundary conditions are viable for utilization; nevertheless, it should be noted that there can be considerable variations in the obtained results. Uncertainties in the conceptual model, and the numerical model, are discussed and ideas for further studies are presented. In conclusion, the geological model is the key conceptual uncertainty. All boundary condition combinations that were tested are applicable, with the most significant differences emerging during pumping events when the system is stressed. An understanding of the system and the model itself is essential for identifying uncertainties and recognising their impact on the modelling results.
Keywords: Groundwater modelling, Groundwater model uncertainty, Conceptual model, Numerical model, MODFLOW2005, Flopy, Glaciofluvial deposit